Disability prevention with early screening and intervention among children with congenital clubfoot in India - Aggarwal, Alisha; Aggarwal, Anisha (International Journal of Research in Orthopaedics, 2020)
Background: Congenital clubfoot has an incidence of 1-9/1000 live births. Untreated clubfoot leads to physical, social, psychological, and financial burden on the family and society. Early intervention can prevent disability in the future. The aim of this study is to assess the effectiveness of an early intervention and conservative management to treat congenital clubfoot and prevent disability. Methods: We conducted a retrospective analysis at an urban multispecialty hospital in North India among children with a diagnosis of congenital clubfoot managed with Ponseti technique (manipulation, casting, tenotomy and bracing). Descriptive statistics and chi-square test were used to measure association between variables. Results: We had a total of 125 feet (41 bilateral, 43 unilateral). 78.5% (n=66) children were below 12 months of age with a mean age at diagnosis of 7.8 months. 70.2% (n=59) children were corrected with less than 5 casts to achieve complete correction. Tenotomy was required in 69% of children (n=58) and was statistically significant. A 100% success rate was achieved in our study. Conclusions: Early intervention is essential to correct idiopathic/ congenital clubfoot, prevent disability and improve quality life in adulthood. National programs with a focus on prevention, surveillance, advocacy, and research are vital for universal health coverage.